Development of Security Model for Protecting Data in the Cloud Using 3-TIER Authentication - A. Onyekachi, Agbakwuru; D. Okechukwu, Njoku; Amanze, B. Chibuike, Amanze (International Journal of Computer Sciences and Engineering, 2021)
This paper focuses on developing a security model for cloud computing to enhance the security for data stored in the database. Therefore this paper is providing a solution by designing a model for securing and protecting data in the cloud computing platform using National Identity Number (NIN), One Time Password (OTP) and Advanced Encryption Standard (AES). The design are simulated using a web-system developed with PHP, MySQL and JavaScript. The System Design followed the OOADM methodology for computerization of the system Modules giving room for coupling, decoupling, modification, encapsulation and reuse, as well as easy maintainability. Unified Modeling Language (UML) was extensively used to simplify the explanation of the system Modules. The software performance was tested using speed of data retrieval and security of the data protection. The security looks at the ability of the system to determine fraudulent users and deny them access to the system. The result obtained from the new system developed shows a high level of data security level as compare to existing system that uses only password for authentication.